The Influence of Green Marketing Communication and Green Influencer Expertise on Green Purchase Behavior at Brand N'Pure - Khairiyyah, Siti; Dedu, May (Journal Research of Social Science, Economics, and Management, 2026)
The beauty industry in Indonesia has experienced rapid growth in recent years, particularly in the skincare sector, accompanied by a significant shift in consumer behavior toward environmentally friendly and sustainable products. This phenomenon, known as green consumerism, has compelled brands to adopt green marketing strategies while also giving rise to challenges such as greenwashing. In this context, the role of influencers with credible expertise in conveying green messages has become increasingly important in shaping consumer purchasing decisions. This research aims to analyze the influence of green marketing communication and green influencer expertise on green purchase behavior. A quantitative method with a survey approach was employed, with data obtained through the distribution of questionnaires to 170 respondents and processed using SPSS with multiple linear regression analysis. The results show that green marketing communication and green influencer expertise simultaneously have a significant effect on green purchase behavior, with an F-test significance value of 0.000. A coefficient of determination (R²) of 0.631 indicates that 63.1% of the variation in green purchase behavior can be explained by both independent variables in the model, while the remainder is attributable to other variables outside the scope of the study. Partially, green influencer expertise has a positive and significant effect on green purchase behavior, while green marketing communication shows a significant effect in the negative direction based on the regression model results. The credibility and expertise of influencers are thus the most dominant variables in influencing respondents' green purchasing behavior